Unique microbial communities in ancient volcanic ash layers within deep marine sediments are structured by the composition of iron phases - Rolfes, Sönke; Longman, Jack; Pahnke, Katharina; Engelen, Bert (Frontiers in Microbiology, 2025)
Much of the marine sedimentary environment is affected by the deposition of tephra, the explosive products of volcanic eruptions. These tephra layers’ geochemical and physical properties often differ substantially from those of the surrounding sediment, forming an extreme carbon-lean environment within the anoxic deep biosphere. Despite this, evidence suggests tephra layers harbor diverse and abundant microbial communities. While little is known about the composition of these communities and even less about their life modes, there is evidence indicating that iron (Fe) plays a vital role for these microorganisms. Here, we aim to link differences in the iron content of tephra layers and surrounding sediments with changes within microbial communities. We combined next-generation sequencing of 16S rRNA genes with geochemical analyses of Fe phases preserved in ancient tephra and sediments recovered from the Norwegian Margin during Expedition 396 of the International Ocean Discovery Program (IODP). In these samples, basaltic tephra contained nearly double Fetotal as surrounding sediments, with the majority hosted in “reducible” Fe(III) oxides, whilst sedimentary Fe is primarily in “easily reducible” Fe(III) oxides. Basaltic tephra harbored distinct microbial communities that differed from the surrounding sediment in composition and predicted metabolic properties. These predictions suggest a higher potential for the assimilatory use of more complex Fe(III) sources in tephra, indicating the microbes are able to exploit the “reducible” Fe(III) found in high quantities in these layers. Our findings confirm the few previous studies that have suggested distinct microbial communities to occur in marine tephra layers. Deciphering the role of iron for indigenous microorganisms hints at how life might flourish in this extreme environment. This has implications for understanding tephra layers as a ubiquitous component of the deep biosphere.